2015
DOI: 10.1071/an14484
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural adaptation of grazing dairy cows to changes in feeding management: do they follow a predictable pattern?

Abstract: Research conducted over recent decades to improve understanding of the functional responses among sward characteristics, intake rate and grazing behaviour has been reviewed. The opportunities to modify grazing pattern by changes in feeding management are discussed and the implications for dairy-farm feeding strategies are highlighted. Progress in the understanding of the functional responses between sward characteristics and intake rate and their main components (bite mass, bite area, bite depth and bite rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
4
19
0
20
Order By: Relevance
“…The length of the first meal (198 min) for CSC LowRFI and CSC HighRFI fell within ranges reported in the literature (Soca et al, 2014;Chilibroste et al, 2015). Compared with CSC HighRFI , CSC LowRFI had a shorter first meal, but this meal represented a larger proportion of the total morning grazing time and the interval between the first and second meal was shorter.…”
Section: Short Communicationsupporting
confidence: 56%
“…The length of the first meal (198 min) for CSC LowRFI and CSC HighRFI fell within ranges reported in the literature (Soca et al, 2014;Chilibroste et al, 2015). Compared with CSC HighRFI , CSC LowRFI had a shorter first meal, but this meal represented a larger proportion of the total morning grazing time and the interval between the first and second meal was shorter.…”
Section: Short Communicationsupporting
confidence: 56%
“…(Jones & Condit, 1948) Tropical areas have short dim morning and afternoon areas from the equator, the longer the duration of the dim morning and afternoon. (Chilibroste et al, 2015) This condition causes the outdoor area continuously exposed to sunlight, which means the increasing the insolation throughout the surface area, such as building facade and ground area. (Wang & Liu, 2002) Meanwhile, it is suggested that buildings are exposed to sunlight at least for 4 hours, so that the buildings are protected from humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Forraje desaparecido: Resumen de las variables seleccionadas para el modelo de regresión múltiple por método de selección stepwise (SAS, 2010). la estructura original de la pastura (masa y altura de forraje previo al pastoreo) afecta la tasa de consumo, la eficiencia de utilización y el consumo total de MS. En una revisión reciente (Chilibroste et al, 2015) han demostrado el impacto del tiempo de acceso la pastura sobre el tiempo efectivo de pastoreo de los animales y en consecuencia sobre la eficiencia de cosecha de forraje por unidad de tiempo. Los antecedentes de estudio del efecto de la AF sobre el CMS no han incluido hasta el momento la variable tiempo de acceso a la pastura (Delagarde y O´Donovan, 2005).…”
Section: Forraje Desaparecidounclassified